2021
DOI: 10.4269/ajtmh.20-1478
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 in Africa: Survey Analysis of Impact on Health-Care Workers

Abstract: As coronavirus disease 2019 (COVID-19) spreads across Africa, little is known about the impact of the pandemic on health-care workers (HCWs) in the region. We designed an anonymous survey distributed via e-mail and phone messaging to 13 countries through the African Hepatitis B Network. We obtained 489 analyzable responses. We used risk ratio analysis to quantify the relationship between binary variables and χ2 testing to quantify the statistical significance of these relationships. Median age of respondents w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 16 publications
2
23
0
Order By: Relevance
“…Measures of increased risk of infection in HCWs versus the general population have been demonstrated in many global studies, with adequate personal protective equipment (PPE) provision and use being key to minimising this risk 15 17 21 24. In resource-constrained settings such as Kita, key tools for protecting HCWs, along with early disease detection, are often limited or absent in Africa 25 26. Measures to improve protection for doctors and nurses, especially considering low levels of health staff availability in the country—in 2017 Mali had only six qualified providers per 10 000 inhabitants—would be pertinent 27…”
Section: Discussionmentioning
confidence: 99%
“…Measures of increased risk of infection in HCWs versus the general population have been demonstrated in many global studies, with adequate personal protective equipment (PPE) provision and use being key to minimising this risk 15 17 21 24. In resource-constrained settings such as Kita, key tools for protecting HCWs, along with early disease detection, are often limited or absent in Africa 25 26. Measures to improve protection for doctors and nurses, especially considering low levels of health staff availability in the country—in 2017 Mali had only six qualified providers per 10 000 inhabitants—would be pertinent 27…”
Section: Discussionmentioning
confidence: 99%
“…A first striking result is the self-reported lack of material and psychological support offered to health workers during the COVID-19 pandemic: although participants reported being informed about the COVID-19 pandemic, most declared not having enough protective personal equipment. That lack of personal equipment has been reported not only among other African countries (Quadri et al, 2021 ) but also in many other countries (Delgado et al, 2020 ; Hakim et al, 2021 ; Martin-Delgado et al, 2020 ; Savoia et al, 2020 ; Tabah et al, 2020 ). Participants also reported not having enough opportunities to benefit from psychological support.…”
Section: Discussionmentioning
confidence: 75%
“…Many studies in Western countries and in Asia have reported a high prevalence of mental health problems among health workers facing COVID-19 (Lai et al, 2020 ; Li et al, 2020 ; Liang, Chen, et al, 2020 ; Liang, Wu, et al, 2020 ; Liu et al, 2020 ). However, data from Sub-Saharan Africa are scarce (Quadri et al, 2021 ), while the pandemic has also dangerously spread over the African continent.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With more oncological AI platforms being proposed in the post-COVID-19 era, it may be that the refocusing of experienced health personnel towards pandemic control did motivate the search for automated tools aimed at facilitating the diagnosis, treatment selection, and prognostication of cancer patients [ 22 - 24 ]. Also, these tools may have been proposed with the aim of increasing the efficiency of specialists, easing the case burden caused by a worsening health provider-to-patient ratio [ 25 ], and limiting person-to-person contact to clinical encounters of utmost importance [ 26 ].…”
Section: Implementation and Potential Refinements For Cancer-based Ar...mentioning
confidence: 99%